2012
DOI: 10.1177/0310057x1204000315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Datex-Ohmeda Aestiva® and Aisys® anaesthetic machines for use in malignant hyperthermia susceptible patients

Abstract: Preparation of anaesthesia machines for use by malignant hyperthermia susceptible patients requires purging the machines of halogenated anaesthetic agents. The endpoint of this process is to reach a gas concentration of 5 ppm or less, which has been arbitrarily chosen as the safe limit of exposure to avoid triggering a malignant hyperthermia event. We examined the washout characteristics of sevoflurane and desflurane from the Datex-Ohmeda Aestiva ® Anaesthesia System and Aisys ® Anaesthesia Carestation ® anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Also, the Aestiva exhibited a more gradual biphasic decrease in concentration because of a breathing system equivalent to twice the volume of the ABS, predisposing to a greater degree of incomplete mixing . Prior studies have suggested the breathing system may contribute to incomplete mixing and pockets of trapped gas . Also, similar washout times were recorded using an autoclaved ABS and no ABS confirming the ABS as a source of anesthetic gases.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Also, the Aestiva exhibited a more gradual biphasic decrease in concentration because of a breathing system equivalent to twice the volume of the ABS, predisposing to a greater degree of incomplete mixing . Prior studies have suggested the breathing system may contribute to incomplete mixing and pockets of trapped gas . Also, similar washout times were recorded using an autoclaved ABS and no ABS confirming the ABS as a source of anesthetic gases.…”
Section: Discussionmentioning
confidence: 72%
“…This study utilized the maximum flow rate of 15 lpm, and one machine representing each model to standardize testing conditions. Reduction of high flow rates to demonstrate the rebound phenomenon was not performed, because this has been well documented . The washout times for the Avance and Aisys were within the MHAUS recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone products incorporated into these machines absorb inhalational anesthetics and result in prolonged release of the agent. Flushing of these machines can take longer that 60 min to achieve a safe level of agent [ 168 ]. A vapor-free anesthetic machine would eliminate this problem but it is likely that most anesthetic departments do not have such a machine available.…”
Section: Reviewmentioning
confidence: 99%
“…Se debe priorizar evitar los fármacos desencadenantes (anestésicos halogenados y relajantes neuromusculares). Para evitar que ninguna partícula de gas halogenado pase al paciente en riesgo de sufrir una HM, es preciso dejar ciclando la máquina de anestesia un tiempo que depende del tipo de máquina (13) , nosotros empleamos una Datex-Ohmeda Aestiva, motivo por el cual dejamos ciclando la máquina a altos flujos más de 90 minutos (13) .…”
Section: Resultsunclassified